Clinical utility of oral Nemonoxacin 500 mg once daily for the treatment of acute lower urinary tract infections: a prospective open-label, multicenter study - Zhen Du; Bo Zheng; Shan Chen; Liang Cui; Huilin Wu; Zhan Gao; Jin Yang; Gang Cui; Jiajing Wang; Tiehuan Shu; Ninghan Feng; Ludong Qiao (BMC Infectious Diseases)
Abstract Background Urinary tract infection (UTI) is one of the most common infectious diseases requiring convenient and appropriate treatment. Nemonoxacin is active against the common pathogens of UTIs. However, more clinical data are required to further support the utility of 500 mg nemonoxacin once daily in treatment of acute lower UTI. Methods We conducted a prospective, single-arm, open-label, multicenter clinical trial in outpatients with acute lower UTI, including uncomplicated UTI (uUTI), recurrent UTI (rUTI), and complicated UTI (cUTI). The patients were prospectively enrolled to take 500 mg nemonoxacin capsules once daily for 3 days (uUTI and rUTI) or 14 days (cUTI). The baseline data, clinical symptoms, laboratory and microbiological tests were analyzed to evaluate the efficacy and safety of nemonoxacin. The clinical and microbiological efficacy were evaluated using the modified intent-to-treat (mITT) set and microbiologically modified intent-to-treat (m-mITT) set, respectively. The comprehensive efficacy and safety were assessed using microbiologically evaluable (ME) set and safety set (SS), respectively. Results A total of 404 patients were enrolled. Majority (90.1%) of the patients were females. More than half (66.3%) of the patients were 20 to 40 years of age, and 19.1% were elderly patients (≥ 60 years). Most (83.2%) of the patients reported two or more urinary tract symptoms. The overall clinical efficacy rate of nemonoxacin was 83.9% (292/348) in mITT set, specifically, 83.9% (186/224) in uUTI, 84.4% (81/96) in rUTI and 89.3% (25/28) in cUTI. The overall microbiological efficacy rate was 76.8% (119/155) in m-mITT set. The overall comprehensive efficacy rate was 73.4% (102/139) in ME set. The incidence of clinical adverse reactions was 7.2% (29/404) in the safety set. Most of the adverse events were mild and transient, including pruritus, nausea, dizziness, and headache. No drug-related serious adverse events were observed. Conclusions Nemonoxacin capsules 500 mg once daily is effective, safe, and well-tolerated for treatment of mild-to-moderate acute lower UTIs in adult outpatients. Trial registration Chinese Clinical Trial Registry (ChiCTR2100046585). Registered on May 22, 2021.